River morphology - Garde, R. J. (New Age International, 2006)
RIVER MORPHOLOGY synthesizes the contributions made by geologists, geomorphologists, geographers, hydraulic engineers and hydrologists and presents a coherent text which takes a balanced view about formation on alluvial rivers and their hydraulics, and analysis of their response to natural and man-made disturbances. The text covers discussion about history of fluvial hydraulics and geomorphology, drainage basin characteristics, soil erosion, fluvial morphology, principles of sediment transport and hydraulics of alluvial and gravel-bed rivers, river bed and channel changes, palaeo-hydraulics, analytical and numerical modeling of alluvial stream transients, morphology of some Indian rivers, rivers and environment, and data needs for morphological studies. Inclusion of two chapters on modeling offers valuable tools for quantitative analysis of a number of problems in alluvial stream transients. RIVER MORPHOLOGY should be useful to undergraduate and graduate students in geology and engineering, to those interested in rivers and involved in planning and management of rivers. Contents: Introduction Drainage Basins and Channel Networks Soil Erosion and Sediment Yield Fluvial Morphology Hydraulics of Alluvial Streams Hydraulic Geometry and Plan Forms of Alluvial Rivers Gravel-Bed Rivers Fluvial Palaeo-hydrology Bed- Level Variation in Streams River Channel Changes Analytical Models of River Morphology Numerical Models for Morphological Studies Morphology of Some Indian Rivers Rivers and Environment Data Requirements for Morphological Studies.